Análisis ergonómico con el método checklistocra en trabajadores de una industria alimentaria - Laverde Albarracin, Cristian (2018)
The disorders produced by repetitive movements, produce serious damages to the health of the workers, the investigation was carried out in the personnel of the line of slaughter of cattle of a company of Santo Domingo de los Tsáchilas from June to September of 2017 in order to evaluate repetitive movements (MR) of upper limbs, their characteristics, relationship with working conditions and other factors. It was used as a tool, the ergonomic analysis of the position, the application of the ergonomic method CheckListOcra and the specific medical examination. In the indentation position, the evaluation was carried out, where activities similar to the rest of the posts in the line are carried out. We identified 11 cycles of actions, all performed repetitive movements as well as other ergonomic risks, we also ranked the work stages where the repetitive activities were higher in frequency in actions 6, 8,9 and 11 with a duration of 3 seconds. Corroborated with the specific medical analysis to the 55 employees and it was reported that 40% are positive to the physical examination, 56% to the neurological examination and the ergonomic method determined high risks for the right upper extremity and middle in the upper extremity left.